RELATIONSHIPS BETWEEN ADAPTIVE AND MALADAPTIVE PERFECTIONISM AND PERCEIVED PARENTING STYLES IN A SAMPLE OF UNIVERSITY STUDENTS - Kontrimienė, Simona (Acta Paedagogica Vilnensia, 2014)
Perfectionism often leads to young adults’ strivings to perform exceptionally in educational settings, which sometimes happens at the expense of their psychological well-being. Recent views of perfectionism have proposed a multidimensional conceptualisation of the construct in which positive or adaptive aspects of perfectionism are distinguished from those which are negative or maladaptive. These approaches vary with respect to the number and definition of factors or components which make up the construct, but the distinction between positive, functional, adaptive or healthy perfectionism and negative, dysfunctional, maladaptive or unhealthy perfectionism is a common feature. Slaney et al. (2001) assess perfectionism with the help of the Almost Perfect Scale-Revised (APS-R). The APS-R is a 23-item inventory designed to measure perfectionism through three subscales: Standards, Discrepancy and Order. The instrument was used in this study to measure adaptive and maladaptive perfectionism in a sample of 149 undergraduate students at Vilnius university.To build on the understanding of the etiology of perfectionism, the study aimed at exploring relationships between students’ two types of perfectionism and their perceived parenting styles. The other instrument used was the Parental Authority Questionnaire (PAQ) (Buri, 1991), which assesses three parenting styles (permissive, authoritarian and authoritative) as conceptualised by Diana Baumrind.The study has found significant positive correlations between adaptive perfectionism and reported authoritative parenting style (r = 0.17, p < 0.05) and maladaptive perfectionism and reported authoritarian parenting style (r = 0.25, p < 0.01).The multiple regression analysis has shown that authoritative parenting is a significant predictor of adaptive perfectionism (β = 0.23, R2 = 0.07), whereas authoritarian parenting is a significant predictor of maladaptive perfectionism (β = 0.37, R2 = 0.11).These findings suggest that parenting experience may influence the development of perfectionistic inclinations, but it is by far not the most salient factor as the multiple regression analysis models account for only 7% and 11% of the variances in the adaptive and maladaptive perfectionism variables. The relationships established in this study are intuitive and call for further hypotheses and research; they also delineate directions for prevention, intervention and postvention programmes.
Keywords: adaptive perfectionism; maladaptive perfectionism; parenting styles